A study on the status quo of PE teachers at private colleges in China - Hua, Z.; Sun. L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The third item of Law for Promoting Private Education was promulgated by the State Council in December, 2002. The law appointed "private education as belonging to the public welfare project and, is an essential part of the socialist education system. China deals with private education by obeying the principle of "encouraging warmly, supporting firmly, leading properly and managing legally." The key is to achieve college Physical Education reform and to achieve the predicted reform results, PE teachers serve as the executors of the reform. Research has shown that the majority of PE teachers` at the professional level in private colleges in China is very low which is potentially harmful to the development of these colleges. Methods A review of documents, expert interviews and survey techniques were used to study the current situation with respect to PE teachers in Shan xi private colleges. The survey involved 462 PE teachers from 20 private colleges (including ten regular colleges and ten vocational colleges). Results The survey findings indicated that the number of teachers in Shan xi private colleges is limited and. the majority of teachers are distributed unevenly. The PE teachers` educational level is low, most being undergraduates and only few postgraduates. There are only a few professors and lecturers and there are more younger teachers and few older ones and with a minimal number of middle-aged teachers. The workload for teachers is heavy, whilethe pay is poor. There is also a lack of skills in foreign languages and lack of technology further hinders the students. Thus, the training systems for PE teachers in Shan xi private colleges are incomplete. The first-class private colleges should have first-class PE teachers. Through comparison and analysis, this study suggests two solutions associated with aspects of the law and regulation and principles in China and the self-construction of private colleges.